2019
DOI: 10.18388/abp.2018_2810
|View full text |Cite
|
Sign up to set email alerts
|

Can vitamin D protect against age-related macular degeneration or slow its progression?

Abstract: Dietary vitamin D plays an important role in maintaining proper vision. Age-related macular degeneration (AMD) is a complex eye disease with unknown pathogenesis. Studies on dietary supplementation and AMD occurrence and progression have produced conflicting results. In its advanced stage, AMD may be associated with apoptosis, pyroptosis or necroptosis of retinal cells. Vitamin D has been reported to play a role in modulating each of these programmed death pathways. Vitamin D is a modulator of the immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 125 publications
0
12
0
1
Order By: Relevance
“…Vitamin D is the regulator of the immune system, which cooperates with CFH and CFI in the complement system and is involved in wAMD pathogenesis [ 51 ]. We found that there was a significant difference in vitamin D3 between the wAMD or CNV and controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D is the regulator of the immune system, which cooperates with CFH and CFI in the complement system and is involved in wAMD pathogenesis [ 51 ]. We found that there was a significant difference in vitamin D3 between the wAMD or CNV and controls.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was a significant difference in vitamin D3 between the wAMD or CNV and controls. Previous studies [ 51 , 52 ] showed that a vitamin D-rich diet can prevent or delay the occurrence and development of AMD, especially CNV. Vitamin D has also been shown to be antiangiogenic [ 53 ], which is involved in cell proliferation, differentiation and apoptosis [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, among the many clinical observations and studies run on the efficacy of vitamins A, C, E, not all the results could confirm their efficacy on the decourse of AMD [396]. As to vitamin D, its role in the prevention of AMD seems to be ascertained, though the amount to be given as food supplement is still in need of better clarification [435].…”
Section: Vitaminsmentioning
confidence: 99%
“…The positive effects of dietary nutrients are largely correlated with autophagy in cancer, neurodegeneration, and many other pathological conditions [30,31]. Vitamins in particular are regulatory of autophagy in various situations, ranging from ocular disease to cancer and disorders of the digestive systems [32][33][34][35][36].…”
Section: Dietary Nutrientsmentioning
confidence: 99%